PENGARUH HARGA JUAL DAN PROMOSI TERHADAP VOLUME PENJUALAN ROUND UP UK.10 LITER PADA TOKO SIHAN LAHAT - hayani yani (Jurnal Manajemen Bisnis Unbara, 2023)
This study aims to determine: (1) The effect of selling prices (2) promotions on UK return up sales. 10 liters and (3) against the sales volume of the UK return up.10 liters on the figure of the devil Lahat. This research is a survey research with an associative design. The population in this study were all consumers of Sihan Lahat figures. The population in this study are selling prices, promotions and sales volume of round up Uk.10 liters at the Sihan Lahat shop which was established from 2001 to 2020. The samples taken in this study are the data table selling prices, promotions and sales volume for 5 years the last one is from 2015 to 2019. Data collection uses a questionnaire that has been tested for validity and reliability. The data analysis technique used in this study is multiple regression analysis. Research results The test results together show (Selling Price) and (Promotion) have a joint effect on Sales Volume, thus the company should pay attention to the two variables that greatly influence the Sales Volume. with a significance level found that (1) the effect of selling price has a positive effect on sales volume, (2) promotion has a positive effect on sales volume and (3) the effect of selling price and promotion has a positive and significant effect on sales volume of Round up uk.10 liters on the character damn Lahat.